2022
DOI: 10.1016/j.omtm.2021.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optogenetic stimulation of the primate retina activates the visual cortex after long-term transduction

Abstract: Over the last 15 years, optogenetics has changed fundamental research in neuroscience and is now reaching toward therapeutic applications. Vision restoration strategies using optogenetics are now at the forefront of these new clinical opportunities. But applications to human patients suffering from retinal diseases leading to blindness raise important concerns on the long-term functional expression of optogenes and the efficient signal transmission to higher visual centers. Here, we demonstrate in non-human pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In laboratory conditions, we and others have reported high spatial and temporal resolution of stimulated RGC activity both for epiretinal electrical (Weitz et al, 2015;Corna et al, 2021) and optogenetic stimulation (Ferrari et al, 2020;Gauvain et al, 2021;Reh et al, 2021;Chaffiol et al, 2022;Khabou et al, 2022). This represents an encouraging result for future vision restoration.…”
Section: Discussionsupporting
confidence: 61%
“…In laboratory conditions, we and others have reported high spatial and temporal resolution of stimulated RGC activity both for epiretinal electrical (Weitz et al, 2015;Corna et al, 2021) and optogenetic stimulation (Ferrari et al, 2020;Gauvain et al, 2021;Reh et al, 2021;Chaffiol et al, 2022;Khabou et al, 2022). This represents an encouraging result for future vision restoration.…”
Section: Discussionsupporting
confidence: 61%
“…Previous research has demonstrated that an AAV2based transduction of the ChrimsonR-TdTomato optogene through intravitreal injection in nonhuman primates resulted in sustained functional expression in the retina for up to 20 months. 125 A few Phase I/II clinical trials of retinal optogenetics for visual restoration have recently been completed and demonstrated general safety of the approach. 126 Clinical translation for cardiac optogenetic therapies has not advanced as quickly as retinal optogenetics as gene and light delivery to the heart is more challenging.…”
Section: Programmingmentioning
confidence: 99%
“…A previous study confirmed that in rodents intravitreally injected with an AAV-channelrhodopsin-2 (ChR2) construct, ChR2 can stabilize expression in the retina and rescue visual function[ 59 ]. In a nonhuman primate study, primates ( Macaca fascicularis ) were intravitally injected with an AAV2 vector with ChR2 to stimulate retinal activation after long-term transfection[ 60 ]. Recently, optogenetics was used to treat a blind patient in a phase 1/2a clinical trial.…”
Section: O Ptogenetics Gene Therapymentioning
confidence: 99%